J‐Aggregation‐Driven Supramolecular Assembly of Dye‐Conjugated Block Polymers: From Morphological Tailoring to Anticancer Applications. (20th September 2021) - Li, Shuoxin; Yan, Xiaosa; Zhang, Junqing; Guo, Xia; Zhang, Yongkang; Su, Meihui; Yang, Chun; Zhang, Hao; Li, Changhua
Abstract: Utilizing the J‐stacking of dyes to drive the assembly of amphiphilic polymers can not only construct supramolecular assemblies with novel architectures but also provide a stabilizing solution for dye J‐aggregation to promote its biomedical applications. However, tightly entangled hydrophobic segments can disrupt the orderly arrangement of dye molecules, thereby preventing dye stacking‐driven supramolecular assembly of block copolymers. Herein, a "molecular glue" strategy is reported that uses the small dye molecule as a molecular glue to restore the J‐stacking of the dye moiety immobilized on the polymer, thereby dominating the supramolecular assembly of the polymer matrix. Very interestingly, the yielded nano‐assembly exhibits a novel worm‐like structure with alternating straight and bent segments. By passing through nanopores, the bent part is disassembled to afford short nanorod NR‐J812 mainly composed of crystalline dye J‐aggregates. It shows favorable colloidal and optical stability, suitable size, and high photothermal property, and demonstrates high performance in photoacoustic imaging and photothermal treatment of tumors in vivo. This work provides important insights into not only the self‐assembly of amphiphilic polymers with novel supramolecular architectures but also the preparation of J‐aggregate materials applicable in vivo, which bring great promise to the biomedical fields. Abstract : A "molecular glue" strategy is presented that uses the small dye molecule as a molecular glue to restore the J‐stacking of the dye moiety immobilized on the polymer, thereby dominating the supramolecular assembly of the polymer matrix. This work provides important insights into not only the self‐assembly of amphiphilic polymers but also the preparation of J‐aggregate materials applicable in vivo.